Cluster-based development in Egypt: A study of external shocks to the leather and medicinal and aromatic plant sectors - Abdelaziz, Fatma; Abdelghany, Nancy; Ellis, Mia; William, Amy; Zhang, Xiaobo (International Food Policy Research Institute, 2021)
The Egyptian government has prioritized the idea of cluster-based development-that is, the geographic concentration of specialized firms, such as in this case, those producing similar or related products. The establishment of such clusters, however, presents significant challenges, bottlenecks, and obstacles. Based on primary field work, this paper focuses on two case studies of the impacts of shocks on business clusters. The first study involved the relocation of an established leather cluster from Cairo to a newly created industrial park, Robbiki Leather City, which was promoted by Egypt’s Ministry of Trade and Industry. Although the relocation partly solved the existing issues of water contamination, new challenges emerged relating to increased production and transportation costs, and unforeseen impacts on the community. The second study assessed the short-term impact of the COVID-19 pandemic on a business cluster producing medicinal and aromatic plants. Overall the MAPs sector was resilient to the outbreak and there are opportunities to offset any negative impacts of the pandemic by taking advantage of new markets for Egyptian MAPs stemming from supply disruptions in other countries; increased global demand for MAPs due to their pharmacological and health properties; and increased international demand for organically grown MAPs. Findings indicate that it is essential for governments to develop responses to the challenges-and especially barriers-to the development of business clusters, while simultaneously supporting and creating incentives for the cooperation, entrepreneurship, and collective action needed for business clusters to thrive and grow. As anticipated, challenges and obstacles-whether overarching or in response to shocks-are unique to specific sectors, contexts, and times, and hence need to be dealt with as an ongoing facilitation process.